The Role of Social Media in Shaping Public Opinion in Society (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Social media has been very successful in shaping public opinion in every society, particularly due to public opinion having now gone so far as to almost disappear forcibly before the power of ruling regimes. In this day and age, social media platforms played their parts through novel communicative methods, widely used across sectors and functions. In fact, this is more than just adding users or building a wide communication network. With attracting more developed audiences, social media has begun making a qualitative impact and has transitioned it as one of the main media networks for informing news and informing opinions. Social media has transformed into the lightning fast way for information and news breaking, and it has become the focus and attention not just of the popular masses but also of more traditional readable and audible media. By juxtaposing the powers of visual and written media over traditional media to this new, increasingly powerful form of online media, which are commonly termed fourth estate resources, social media as a whole can be considered as having overshadowed an earlier era’s glory. This is not due to bias or anything else but because traditional media, from newspapers to television channels, being funded and under the sponsorship of such entities, parties, or prominent figures, is well-established with these affiliations already. Social media, on the contrary, has overtaken and surpassed traditional media in terms of independence and liberation from barriers and allegiances.